Celecoxib‐Induced Change in Atrial Electrophysiologic Substrate in Arthritis Patients. Issue 1 (24th September 2013) - Pizzuto, Katerina; Averns, Henry L; Baranchuk, Adrian; Abdollah, Hoshiar; Michael, Kevin A.; Simpson, Christopher; Redfearn, Damian P.
<x xml:space="preserve">Abstract</x> Background Cyclooxygenase‐2 inhibitors, the newest class of nonsteroidal antiinflammatories, pose an increased risk of adverse cardiovascular events, in particular atrial fibrillation (AF). We hypothesized that the COX‐2 inhibitor celecoxib alters atrial electrophysiology, and thus promotes the development of AF. Methods Three prospective patient cohorts were created: Healthy patients (n = 35), inflammatory arthritis patients with no celecoxib use (n = 22), and inflammatory arthritis patients treated with celecoxib (n = 20). Patients were included in the arthritis cohorts if they were over the age of 18 and had a diagnosis of inflammatory arthritis. Patients in the celecoxib group must be actively treated with celecoxib for more than 2 months. Patients were excluded if they were taking antiarrhythmic mediation, had a diagnosis of AF, refractory hypertension, or congestive heart failure. High‐resolution signal‐averaged electrocardiogram was recorded and P‐wave duration (PWD) was derived. Results PWD was significantly longer in inflammatory arthritis patients treated with celecoxib, compared to both healthy and inflammatory arthritis patients (P = 0.049, P = 0.036). There was no difference in the PWD of healthy patients as compared to inflammatory arthritis patients (P = 0.916). Mean PWD (standard error of the mean) of the inflammatory arthritis patients treated with celecoxib was 133.1 (2.7) ms as compared to 125.3 (1.6) ms in the healthy patients and 124.0 (2.9) ms in the inflammatory arthritis patients. Conclusions Given that PWD is a well‐accepted noninvasive marker of atrial electrophysiology, our results suggest that these patients demonstrate adverse atrial remodeling predisposing to atrial arrhythmia.